Peningkatan Keterampilan Ibu dalam Memantau Perkembangan Batita dan Deteksi Dini Stunting Menggunakan Simulasi Game Jumanji Flash Card - Hasbi, Muhammad; Wijayanti, G. A Sri Puja Warnis; Jafar, Sitti Rusdianah; Purnamawati, Dewi; Zulkifli, Zulkifli; Sentana, Aan Dwi; Mufida, Nur Aini (Poltekkes Kemenkes Mataram, 2024)
Stunting is a serious public health problem faced by several countries, including Indonesia. The reality found in the field is that mothers do not know what child development is and how to assess it. One way to improve mothers' skills in integrating battery development using KPSP as an early detection of stunting is by simulating the Jumanji flash card game. This research aims to find out an overview of the Jumanji flash card game simulation on improving mothers' skills in integrating toddler development using KPSP as an early detection of stunting. Method: This research uses a Pre Experimental design with a One Group Pretest-Posttest design. The research population was mothers of toddlers who had stunting toddlers in the Jempong Barat area, Jempong Village, Karang Pole Community Health Center area. The total sample was 43 respondents. The sampling technique used purposive sampling technique. The results of statistical tests using the Wilcoxon sign shelf test showed that there was an influence of the Jumanji flash card game simulation on increasing mothers' skills in detecting their child's growth and development. Conclusion: The Jumanji flash card simulation game can improve mothers' skills in monitoring toddler development using KPSP as an early detection of stunting. Suggestion: It is recommended that mothers apply the skills of integrating toddler development to determine if the child's development is normal or whether there are deviations.